2013
DOI: 10.1002/ejlt.201200159
|View full text |Cite
|
Sign up to set email alerts
|

Lipid characteristics and phenolics of native grape seed oils grown in Turkey

Abstract: Grape seed oils of seven native Turkish cultivars (namely Atfi, Mazruna, Black Kerküş, Zeyti, Verdani, Karfoki, and Kerküş) were evaluated for their fatty acids, tocols, phytosterols as well as total phenolics and oxygen radical absorbance capacity (ORAC) values. Among the fatty acids, linoleic acid (18:2ω6) was the most abundant (56.38–68.56%), followed by oleic acid (16.45–29.38%, 18:1ω9), palmitic acid (8.19–9.44%, 16:0), and stearic acid (3.74–4.98%, 18:0). Total tocopherols and tocotrienol amounts varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
32
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 26 publications
9
32
2
2
Order By: Relevance
“…The content of -tocotrienol ranged from 325 to 593 mg/kg, -tocotrienol was found between 93.6 and 293 mg/kg and (Heinemann et al, 2008),  . -tocopherol,  . -tocotrienol, and -tocotrienol were the most aboundant components in japonica rice, while in indica rice, the highest mean level was for -tocotrienol, followed by  . -tocopherol and  . -tocotrienol. Tocochromanol composition was in good agreement with the tocopherol composition of several grape seed oils reported in the literature (Wie et al, 2009;Demirtas et al, 2013). With a few exceptions, the percentage of tocotrienols was significantly (P < 0.05) higher in the HMRB than in the WMRB.…”
Section: Tocochromanol Contents In the Rice Bran Cultivarssupporting
confidence: 87%
“…The content of -tocotrienol ranged from 325 to 593 mg/kg, -tocotrienol was found between 93.6 and 293 mg/kg and (Heinemann et al, 2008),  . -tocopherol,  . -tocotrienol, and -tocotrienol were the most aboundant components in japonica rice, while in indica rice, the highest mean level was for -tocotrienol, followed by  . -tocopherol and  . -tocotrienol. Tocochromanol composition was in good agreement with the tocopherol composition of several grape seed oils reported in the literature (Wie et al, 2009;Demirtas et al, 2013). With a few exceptions, the percentage of tocotrienols was significantly (P < 0.05) higher in the HMRB than in the WMRB.…”
Section: Tocochromanol Contents In the Rice Bran Cultivarssupporting
confidence: 87%
“…12 It is controversial whether grape seed oil is a significant source of T3; Crews et al 13 investigated thirty varieties of grape seed oils from Spain, France and Italy, and found that the total content of TPs and T3s was as high as 1208 mg kg −1 comprising mostly (>50%) αT3 and γT3. Conversely, other studies conducted in Canada, Portugal, and Turkey [14][15][16] found that T3 amounts fluctuated significantly between grape varieties ranging from 250-1500 mg kg −1 oil. However, no study has been conducted to evaluate the T3 a Department of Food Science and Human Nutrition, University of Florida, Gainesville 32611, Florida, USA.…”
Section: Introductionmentioning
confidence: 73%
“…Fatty acid profile of the grape seeds oil was performed on a GC HP 6890, equipped with a flame ionization detector and DB 225 MS capillary column (30 m × 0.25 mm × 0.2 µm) as previously described. 16 …”
Section: Determination Of Vitamin E Content and Fatty Acid Compositionmentioning
confidence: 99%
“…Bu sayede hasat süresinin ilk birkaç haftas› boyunca milyonlarca ton üzüm posas› ortaya ç›kmaktad›r. fiarap ve üzüm suyu üretiminden geriye kalan bu posada önemli düzeyde biyoaktif bileflikler bulunmaktad›r (5,6). Üzüm çekirdekleri bu posan›n kuru a¤›rl›k baz›nda %38-52'lik önemli bir k›sm›n› oluflturur (7).…”
Section: Introductionunclassified
“…Bunlar içerisinde üzüm çekirdeklerinin de¤erlendirilmesi ekonomik aç›dan önemli bir yaklafl›m olarak kabul edilmektedir (10). Üzüm çekirdekleri % 7-20 civar›nda ya¤ içermektedir, geri kalan›n› kuru bazda %40 fiber yap›, %7 tanenler gibi karmafl›k yap›da bulunan fenolikler, %11 proteinler, %7'sini su ve iz miktarlarda flekerler ve mineraller oluflturmaktad›r (5,7,11). Hafif meyvemsi lezzeti, genellikle meyvemsi ve turunçgil kokular› veren monoterpenlere (limonen, mirsen, β-pinen vb.)…”
Section: Introductionunclassified